ANÁLISE DE CONFLITOS DA ARBORIZAÇÃO DE VIAS PÚBLICAS UTILIZANDO SISTEMAS DE INFORMAÇÕES GEOGRÁFICAS: CASO IRATI, PARANÁ - MAYER, CLEVERSON LUIZ DIAS (2012)
Street arborization promotes numerous benefits to the urban population’s life quality, however, if it is implanted in an inadequate way, street arborization can cause many disorders to the cities. In this sense, the aim of this study was analysis the conflicts in Irati’s urban forest, Paraná, through spatial analyses technique. It was used the SPRING software for the spatial analysis, using Quickbird satellite’s images of 60cm spatial resolution, and vector files containing the boundary of city neighborhoods, electrical energy transmission system, sewer system and water distribution system, urban equipments and trees location. The alphanumeric data corresponding to the trees, necessary for the SIG elaboration, were provided by the Secretariat of Ecology and Environment of the City. After structuring the data model, was conducted the confrontation of urban structures and location of individual trees concerning the safety distances with the reality observed through appointments to the database and applied the Kernel density estimator to the results of consultations. It was also used the image statistic, applied to the matricial results generated by the density estimator analysis. The results detected 1286 (98.47%) conflicts, i.e., individual trees that did not comply with the recommendations of the relevant legislation concerning its characteristics and the location. With use of Kernel statistic , density images were generated from the results of the consultations, enabling better visual interpretation in the spatial distribution of the conflicts. The images statistic showed that, in general, the conflicts spatial distribution has high correlation between itself, proving the difficulty of deploying street arborization so as not conflicting with the various urban structures, thus demonstrating the necessity for adequation of urban structures for the deployment of trees, and not just a setting for the arborization.